Analyzing Imla’ and I’rab Errors in Grade XI Arabic Textbook of Indonesia’s Ministry Religious Affairs - Wahyu Candra Saputra; Muhammad Zayinil Akhas (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2026)
This study was motivated by the discovery of various imla’ and i’rab errors in the Dars al-Lughah al-Arabiyyah textbook for the eleventh grade published by the Ministry of Religious Affairs of the Republic of Indonesia in 2020, which is used as teaching material in scool. This study aims to identify, classify, and explain the forms of errors in the writing of nominal sentences, verbal sentences, and particles contained in the textbook. The research employed a descriptive qualitative approach using library research methods. The data consisted of words and sentences containing linguistic errors in the textbook, while the data collection techniques were conducted through documentation and content analysis. The results of the study revealed that there were 60 linguistic errors consisting of 30 imla’ errors and 30 i’rab errors. The most dominant imla’ errors were found in the writing of hamzah qaṭh and hamzah waṣl, while i’rab errors mostly occurred in the inappropriate use of final word inflections within grammatical structures, such as errors in maf‘ul bih, iḍafah, tawabi’, and the structure of musnad and musnad ilaih. These findings indicate the need for more careful linguistic revision and editing of Arabic textbooks before they are used in the learning process. Keywords: Error Analysis, Imla’, I’rab, Arabic teaching manual. Penelitian ini dilatarbelakangi oleh ditemukannya berbagai kesalahan imla’ dan i’rab dalam buku Dars al-Lughah al-Arabiyyah kelas XI terbitan Kementerian Agama Republik Indonesia tahun 2020 yang digunakan sebagai bahan ajar di madrasah. Penelitian ini bertujuan untuk mengidentifikasi, mengklasifikasi, serta menjelaskan bentuk-bentuk kesalahan imla’ dan i’rab pada penulisan kalimat isim, fi’il, dan huruf dalam buku tersebut. Penelitian menggunakan pendekatan kualitatif deskriptif dengan jenis penelitian kepustakaan (library research). Data penelitian berupa kata dan kalimat yang mengandung kesalahan bahasa dalam buku ajar, sedangkan teknik pengumpulan data dilakukan melalui dokumentasi dan analisis isi. Hasil penelitian menunjukkan bahwa ditemukan 60 kesalahan bahasa yang terdiri atas 30 kesalahan imla’ dan 30 kesalahan i’rab. Kesalahan imla’ paling dominan terdapat pada penulisan hamzah qath’ dan hamzah wasl, sedangkan kesalahan i’rab banyak terjadi pada ketidaksesuaian harakat akhir kata dalam struktur nahwu, seperti kesalahan pada maf’ul bih, idhafah, tawabi’, dan susunan musnat musnat ilaih. Temuan ini menunjukkan perlunya revisi dan penyuntingan linguistik secara lebih teliti terhadap buku ajar bahasa Arab sebelum digunakan dalam proses pembelajaran. Kata kunci: Analisis kesalahan, Imla’, I’rab, Buku ajar bahasa arab. ينطلق هذا البحث لكثرة الأخطاء الإملائية والإعرابية الواردة في كتاب درس اللغة العربية للفصل الحادي عشر الصادر وزارة الشؤون الدينية الإندونيسيا سنة 2020 م الذي يستخدم لمادة تعليمية في المدارس. ويهدف هذا البحث إلى الكشف عن أشكال الأخطاء الإملائية والإعرابية في كتابة الاسم والفعل والحرف مع تصنيفها وتحليلها وفق القواعد الصحيحة للغة العربية. واعتمد الباحث لمنهج الكيفي الوصفي من خلال الدراسة المكتبية حيث تمثلت البيانات في الكلمات والجمل التي اشتملت على الأخطاء اللغوية في الكتاب وجمع البيانات بأسلوب التوثيق وتحليل المحتوى. وقد أظهرت نتائج البحث وجود ستنين خطأ لغوي منها ثلاثوون خطأ إملائيا وثلاثون خطأ إعرابيا. وكانت أكثر الأخطاء الإملائية شئيعة في كتابة همزة القطع وهمزة الوصل. وتكررت الأخطاء الإعرابية في التركيب النحوية مثل المفعول به والإضافة والتوابع والإسناد. وتدل هذه النتائج على أهمية المراجعة اللغوية والعلمية الدقيقة في كتابته قبل اعتمادها لعمالية التعليمية. الكلمات الرئيسية: تحليل الأخطاء، الإملاء، الإعراب، كتاب درس اللغة العربية